Veterinary Specializations of Secondary Importance. Computer Technology A) Description and Application in certain sciences and education - ΧΑΤΖΙΟΛΟΣ, ΒΑΣ. Κ. (Journal of the Hellenic Veterinary Medical Society, 2019)
Attention of the veterinary student and young veterinarian is drawn to the tremendous importance of computer technology in all the sciences and specifically in veterinary medicine. Initially, the article briefly reviews computer development and alludes to its history, classification, and programming language. Also discussed are the advantage derived from the practical application of computer knowledge to the various endeavors of every-day life in various sciences and in education.